Anatomy of a nonhost disease resistance response of pea to Fusarium solani: PR gene elicitation via DNase, chitosan and chromatin alterations - Hadwiger, Lee A. (Frontiers in Plant Science, 2015)
Of the multiplicity of plant pathogens in nature, only a few are virulent on a given plant species. Conversely, plants develop a rapid “nonhost” resistance response to the majority of the pathogens. The anatomy of the nonhost resistance of pea endocarp tissue against a pathogen of bean, Fusarium solani f.sp. phaseoli (Fsph) and the susceptibility of pea to F. solani f sp. pisi (Fspi) has been described cytologically, biochemically and molecular-biologically. Cytological changes have been followed by electron microscope and stain differentiation under white and UV light. The induction of changes in transcription, protein synthesis, expression of pathogenesis-related (PR) genes, and increases in metabolic pathways culminating in low molecular weight, antifungal compounds are described biochemically. Molecular changes initiated by fungal signals to host organelles, primarily to the chromatin within host nuclei, are identified according to source of the signal and the mechanisms utilized in activating defense genes. The functions of some PR genes are defined. A hypothesis based on this data is developed to explain both why fungal growth is suppressed in nonhost resistance and why growth can continue in a susceptible reaction.